Pengaruh Silase Pakan Komplit Berbasis Sorgum Clitoria Ternatea dengan Penambahan berbagai Level Konsentrat Mengandung ZnSO4 dan ZnCu Isoleusinat terhadap Fermentasi Rumen In Vitro - Consita Putri Epa Hoy; Erna Hartati; Gusti Ayu Y. Lestari (Yayasan Sumber Daya Manusia Cerdas, 2023)
The aim of this research was to determine the rumen fermentability of complete feed silage based on sorghum-Clitoria ternatea with the addition of concentrate containing ZnSO4 and Zn-Cu isoleucinate In Vitro. The method used in this research was an experiment with a Completely Randomized Design (CRD) for 4 treatments with 4 periods as replications. The silage treatments tested consisted of R0: sorghum-Clitoria ternatea silage without concentrate, R10: complete feed silage based on sorghum-Clitoria ternatea with the addition of 10% concentrate, R20: complete feed silage based on sorghum-Clitoria ternatea with 20% concentrate, R30: silage complete feed based on sorghum-Clitoria ternatea with 30% concentrate. The added concentrate contains ZnSO4 and Zn-Cu isoleucinate. The parameters observed were pH, Vollatile Fatty Acid (VFA), and NH3. The results of the research showed that the provision of complete feed silage based on sorghum-Clitoria ternatea with the addition of various levels of concentrate containing ZnSO4 and Zn-Cu isoleucinate had no significant effect (P>0.05) on increasing the pH, VFA and NH3 values. The conclusion of the research shows that giving complete feed silage based on sorghum-Clitoria ternatea with the addition of concentrate containing ZnSO4 and Zn-Cu isoleucinate does not affect the increase in pH values, VFA and NH3 concentrations In Vitro.